STUDI ETNOMATEMATIKA PADA TRADISI LOKAL SEBAGAI KONTEKS PEMBELAJARAN MATEMATIKA - Sape, Herwandi; Syamsuddin, Agustan (Almeera Education, 2025)
This study aims to explore the mathematical elements embedded in the local traditions of the Maros Regency community, South Sulawesi, and analyze how these elements can be integrated into mathematics learning at the senior high school level. A descriptive qualitative approach was employed, utilizing semi-structured interviews with teachers, students, and community figures, along with direct observations of local cultural phenomena. The findings reveal that cultural practices such as traditional weaving patterns, measurement systems in vernacular architecture, and traditional fishing navigation involve mathematical concepts such as symmetry, patterns, ratios, coordinate systems, and estimation. Interviews showed that both teachers and students responded positively to the ethnomathematics approach, although its implementation remains limited due to a lack of training and culturally relevant teaching materials. Meanwhile, community elders served as vital knowledge holders in bridging the understanding between culture and mathematical concepts. These findings emphasize the importance of integrating local culture into education to enhance relevance, conceptual understanding, and to foster students’ cultural identity and pride. The study recommends the development of a structured and sustainable contextual learning model based on local cultural heritage